Antithrombotic Therapy in Patients with Malignant Lymphoproliferative Disorders Treated with Ibrutinib - EI Emelina; GE Gendlin; IG Nikitin (Клиническая онкогематология)

(untitled)
Background. Antithrombotic therapy in chronic lymphocytic leukemia (CLL) patients is challenging, as this category of patients is initially characterized by high risk of hemorrhagic complications. The use of ibrutinib influencing the platelet function constitutes an additional bleeding risk. A crucial task consists in risk minimization of both hemorrhagic complications and thrombosis while sticking to ibrutinib treatment.